AP Psychology - Maitland, Laura Lincoln; Hannah, Pam (5 steps to a 5, 2004)
This book is suitable for the more than one million students taking the AP exams each year. There are boxed quotes offering advice from students who have aced the exams and from AP teachers and college professors. There are sample tests that closely simulate real exams; review material based on the contents of the most recent tests; Icons highlighting important facts, vocabulary, and frequently asked questions; and websites and links to valuable online test resources, along with author e-mail addresses for students with follow-up questions. It is written by authors who are either AP course instructors or exam developers.